Personal reflections on natural history as common ground for interdisciplinary multispecies socio‐ecological research. Issue 1 (19th February 2016) - Root‐Bernstein, Meredith
Abstract : Interdisciplinary research between social and environmental sciences can meet difficulties when attempting to combine qualitative and quantitative field methods. Natural history, largely sidelined from professional science, may have value as a practice with elements common to the social and environmental sciences. In this commentary, I reflect on my own natural history knowledge and practice related to my primary research habitat in central Chile, and how natural history has helped me to generate interdisciplinary approaches. I propose that three key elements of natural history practice in an interdisciplinary context are observation, interpretation, and the human context of engagement with nature. Natural history practice can help to build consensual knowledge and trust within interdisciplinary teams. It can also generate novel research directions through a return to direct engagement with nature. Abstract : Interdisciplinary research between social and environmental sciences can meet difficulties when attempting to combine qualitative and quantitative field methods. Natural history, largely sidelined from professional science, may have value as a practice with elements common to the social and environmental sciences. In this commentary, I reflect on my own natural history practice related to my primary research habitat in central Chile, and how it has helped me to generate interdisciplinary approaches. e00015 Drawing, remembering, knowing: natural history and the ecological imagination